THE LEGAL PROBLEMS OF ESTABLISHING THE ADDITIONAL GUARANTEES OF REALIZATION OF CONSTITUTIONAL HUMAN AND CIVIL RIGHTS AND FREEDOMS BY THE CONSTITUENT ENTITIES OF THE RUSSIAN FEDERATION - A. Chuklin (Правоприменение, 2018)
The subject. The article focuses on the need to improve legislative and law enforcement activities related to the consolidation of constituent entities of the Russian Federation additional guarantees of realization of constitutional human and civil rights and freedoms.The purpose of the article is to identify main ways of improvement the legal regulation additional guarantees of realization of constitutional human and civil rights and freedoms by the constituent entities of the Russian Federation.The methodology. The author uses a dialectical method, a method of analysis and synthesis, a formal legal method.The results and scope of application. The lack of unity in understanding the essence of additional guarantees of realization of rights and freedoms requires not only theoretical analysis of this legal category, but a consistent system of the legislation, and corresponding to the system of law enforcement practice. The legal establishment of the additional guarantees of realization of constitutional human and civil rights and freedoms, due solely to the will of the legislator of a constituent entitiy of the Russian Federation aimed at the concretization of constitutional rights and freedoms as well as of the security mechanisms (legal conditions, means) of the implementation of these rights. Features of development of the corresponding constituent entitiy of the Russian Federation should be taken into account.One of the main directions of improvement of legal regulation in this field is legislative recognition of additional guarantees of realization of constitutional human and civil rights and freedoms established by the constituent entities of the Russian Federation. This concept should be reflected in the Federal law of October 6, 1999 No. 184-FZ "On General principles of organization of legislative (representative) and executive bodies of state power of constituent entities of the Russian Federation", as well as in the constitutions (charters) of constituent entities of the Russian Federation. The consolidation of this concept in the legislation will be the impetus to the theoretical analysis of this legal category, and will ultimately contribute to the improvement of the legal status of the individual.Conclusions. Improvement of regional legal policy in the sphere of establishment additional guarantees of realization of constitutional human and civil rights and freedoms by subjects of the Russian Federation has great practical significance and contributes to the theoretical knowledge of the specified legal category.